Interpretation of equine laboratory diagnostics - Pusterla, Nicola, 1967-; Higgins, Jill, 1977- (John Wiley & Sons, Inc., 2018)
"Interpretation of Equine Laboratory Diagnostics offers a comprehensive approach to equine laboratory diagnostics, including hematology, clinical chemistry, serology, body fluid analysis, microbiology, clinical parasitology, endocrinology, immunology, and molecular diagnostics"- Resumé vydavatel
Keywords: koně; nemoci živočichů; veterinární diagnostika; animals diseases; horses; veterinary diagnostics; elektronické knihy; sborníky; electronic books; papers of several authors